QUR'AN-BASED MATHEMATICS LEARNING DESIGN ON THE SET MATERIAL FOR JUNIOR HIGH SCHOOL STUDENTS - Rahmy Zulmaulida; Dwi Syifa Kusumawati; Mahdalena Mahdalena (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
This study aims to develop a valid and effective Al-Qur'an-based mathematics learning design to be used as a choice of teaching materials for educators. The method used is the research and development method according to Borg and Gall, with the steps contained in this study: 1) Potential and Problems; 2) Data Collection; 3) Product Design; and 4) Product Validation and Trial. The study was conducted on three junior high schools with high, medium, and low levels. Each school was taken one class to be tested.  The results showed: This learning is different from ordinary mathematics learning, because it will increase understanding of the verses of the Qur'an that contain mathematical concepts. Based on the results of the product validation test (RPP, learning books, and LKPD) obtaining a percentage score above 76 and being included in the very feasible category, the product is valid. The student's response to the product gets a percentage score of ≥ 60, which is included in the positive category; the product can be said to be practical. While the effectiveness of learning is assessed from the activities of students with a very good category, namely the percentage value ≥ 90, and the learning outcomes of students individually and classically get good results, So it can be concluded that the learning design developed is effective to use.Penelitian ini bertujuan untuk mengembangkan desain pembelajaran matematika berbasis Al-Qur'an yang valid dan efektif untuk digunakan sebagai pilihan bahan ajar bagi tenaga pendidik. Metode yang digunakan adalah metode penelitian dan pengembangan menurut Borg and Gall, dengan langkah-langkah yang terdapat dalam penelitian ini: 1) Potensi dan Permasalahan; 2) Pengumpulan Data; 3) Desain Produk; dan 4) Validasi dan Uji Coba Produk. Penelitian dilakukan pada tiga sekolah menengah pertama dengan tingkat tinggi, sedang, dan rendah. Setiap sekolah diambil satu kelas untuk diuji.  Hasil penelitian menunjukkan: Pembelajaran ini berbeda dengan pembelajaran matematika biasa, karena akan meningkatkan pemahaman ayat-ayat Al-Qur'an yang memuat konsep-konsep matematika. Berdasarkan hasil uji validasi produk (RPP, buku pembelajaran, dan LKPD) memperoleh skor persentase di atas 76 dan masuk dalam kategori sangat layak, produk tersebut valid. Respon siswa terhadap produk mendapatkan skor persentase ≥ 60, yang termasuk dalam kategori positif; Produk tersebut bisa dikatakan praktis. Sedangkan efektivitas pembelajaran dinilai dari aktivitas siswa dengan kategori sangat baik yaitu nilai persentase ≥ 90, dan hasil belajar siswa secara individu dan klasik mendapatkan hasil yang baik, Sehingga dapat disimpulkan bahwa desain pembelajaran yang dikembangkan efektif untuk digunakan.